IMAGES OF BOATS IN NORTHERN EURASIA - A. S. Kulikova (Вестник Кемеровского государственного университета, 2014)
The paper analyzes the images of boats on the material petroglyphs of two natural and historical areas of Northern Europe and Northern Asia. The boat serves as a generalized name of all water means of transportation. The relations of rock art sites with geological environment are examined. The author makes conclusions about the two areas of rock art in the Eurasian space and the functionality of water means of transportation.